Large herbivores facilitate a dominant grassland forb via multiple indirect effects. Issue 4 (3rd March 2022) - Zhong, Zhiwei; Li, Xiaofei; Smit, Christian; Li, Tianyun; Wang, Ling; Aschero, Valeria; Vázquez, Diego; Ritchie, Mark; Cushman, J. Hall; Wang, Deli
Abstract: While large herbivores are critically important components of terrestrial ecosystems and can have pronounced top‐down effects on plants, our understanding of the underlying mechanisms driving these effects remains incomplete. Large herbivores can alter plant growth, reproduction, and abundance through direct effects (predominantly consumption) and through indirect effects via altered interactions with abiotic factors and other species. We know considerably less about these indirect effects than the direct effects. Here, we integrate medium‐ and small‐scale field experiments to investigate how a large vertebrate herbivore, cattle ( Bos taurus ), affects the aboveground biomass of a dominant forb species, Artemisia scoparia, via diverse direct and indirect pathways in a temperate grassland in northeast China. Although cattle consumed this forb, its biomass increased significantly in response to grazing, due to multiple indirect positive effects that outweighed the direct negative effects of consumption. Cattle preferentially consumed the competing grass Leymus chinensis, and altered Artemisia microhabitats by reducing total plant cover and litter biomass and by increasing the abundance of co‐occurring ant species (e.g., Formica spp. and Lasius spp.). This led to additional indirect positive effects on A. scoparia likely due to (1) increased light availability in understory layers and other limiting resources (e.g., soil nutrients and moisture) caused by removal of competitors and plant litter at the soil surface and (2) the changes in resource availability (e.g., soil nutrients and moisture) associated with ant colonies. Our results show that large herbivores can affect plant growth not only via direct consumption, but also via multiple indirect effects. Focusing on the causes and consequences of herbivore‐induced indirect effects will not only help us to better understand the influence of these animals in ecological systems, but will also lead to more effective land management and conservation practices in the regions they inhabit.